Genetic, histochemical and biochemical studies on goat TSE cases from Cyprus. (December 2016) - Niedermeyer, Susanne; Eiden, Martin; Toumazos, Pavlos; Papasavva-Stylianou, Penelope; Ioannou, Ioannis; Sklaviadis, Theodoros; Panagiotidis, Cynthia; Langeveld, Jan; Bossers, Alex; Kuczius, Thorsten; Kaatz, Martin; Groschup, Martin; et al.
Abstract Scrapie and bovine spongiform encephalopathy (BSE) are transmissible spongiform encephalopathies (TSE's) affecting sheep and goats. Susceptibility of goats to scrapie is influenced by polymorphisms of the prion protein gene (PRNP) of the host. Five polymorphisms are associated with reduced susceptibility to TSE's. In the study presented here caprine samples from a scrapie eradication program on Cyprus were genotyped and further characterized using BioRad TeSeE rapid test, histological, immunohistochemical and biochemical methods. In total 42 goats from 20 flocks were necropsied from which 25 goats showed a positive result in the rapid test, a spongiform encephalopathy and an accumulation of pathological prion protein (PrPSc ) in the obex. PrPSc deposits were demonstrated in the placenta, peripheral nervous and lymphoreticular system. Two animals showed PrPSc -accumulations in peripheral tissues only. By discriminatory immunoblots a scrapie infection could be confirmed for all cases. Nevertheless, slight deviations in the glycosylation pattern might indicate the presence of different scrapie strains. Furthermore scrapie samples from goats in the current study demonstrated less long term resistance to proteinase K than ovine or caprine BSE control samples. Reduced scrapie susceptibility according to the PRNP genotype was demonstrated (Fishers Exact test, p < 0.05) for the goats with at least one polymorphism (p = 0.023) at the six codons examined and in particular for those with polymorphisms at codon 146 (p = 0.016). This work characterizes scrapie in goats having implications for breeding and surveillance strategies.